Genome Resequencing, Improvement of Variant Calling, and Population Genomic Analyses Provide Insights into the Seedlessness in the Genus Vitis - Myung-Shin Kim; Youn Young Hur; Ji Hong Kim; Soon-Chun Jeong (G3: Genes, Genomes, Genetics, 2020)
The seedlessness of grape derived from stenospermocarpy is one of the most prized traits of table or raisin grapes. It is controlled by a complex genetic system containing one dominant gene and multiple recessive genes. Here, we collected dense variation data from high-depth resequencing data of seeded, seedless, and wild relative grape genomes sequenced to > 37x mean depth. Variant calls were made using a modified variant calling pipeline that was suitable for highly diverse interspecific grape accessions. The modified pipeline enabled us to call several million more variants than the commonly recommended pipeline. The quality was validated by Sanger sequencing data and subsequently supported by the genetic population structure and the phylogenetic tree constructed using the obtained variation data, results of which were generally consistent with known pedigree and taxonomic classifications. Variation data enabled us to confirm a dominant gene and identify recessive loci for seedlessness. Incidentally, we found that grape cultivar Rizamat contains an ancestral chromosomal region of the dominant gene in Sultanina, a predominant seedlessness donor cultivar. Furthermore, we predicted new candidate causal genes including Vitvi01g00455, Vitvi08g01528, and Vitvi18g01237 associated with the recessive seedless-regulating loci, which showed high homology with genes that regulate seed development in Arabidopsis. This study provides fundamental insights relevant to variant calling from genome resequencing data of diverse interspecific hybrid germplasms such as grape and will accelerate future efforts aimed at crop improvement.